The digitalization of politics and return to television. The case of the Argentinian candidates on Facebook - Slimovich, Ana (2019)
The crisis in mass media and the emergence of internet based media have generated mutations in political discourses. In this paper we will focus on the study of one aspect of the digitalization of politics: media interaction. We use tools of socio-semiotics, the mediatization of politics theory and theories of new media. The corpus consists of accounts in Facebook of the candidates for president in the election of 2011 in Argentina. Our hypothesis is that digital politics discursivities involve operations of apropiation of television discourses.